The Sm-Nd isotopic method in the geochronology laboratory of the University of Brasília - GIOIA,S.M.C.L. (2000)
Nd isotopes represent one of the best tools to investigate the processes involved in the evolution of the continental crust and mantle. This is due mainly to the similar geochemical behaviour of Sm and Nd, both light rare earth elements, which inhibits their fractionation during most varied geological processes. In order to carry out crustal evolution studies in central Brazil, the Sm-Nd isotopic method was implanted at the Geochronology Laboratory of the University of Brasília. The Sm-Nd separation methodology is basically that described in Richard et al. (1976), with the addition of some improvements. In this study we describe in detail the methodology used in Brasília. Precision and accuracy were checked with the international standards such as JB-3, BCR-1, BHVO-1 and La Jolla, and the following results were found: JB-3 (Nd=15.74 ppm and Sm=4.28 ppm), BCR-1 (143Nd/144Nd=0.512647±8, Nd=28.73 ppm and Sm=6.66 ppm), BHVO-1 (Nd=24.83 ppm and Sm=6.2 ppm) and La Jolla (143Nd/144Nd=0.511835±14).